Transnational migration and dual career of Slovenian and Swiss elite female handball players - A longitudinal analysis - Bon, M.; Doupona, M.; Wilson-Gahan, S.; Capranica, L.; Guidotti, F. (Sports, 2022)
The purpose of this study was to identify the career paths of transnational migrating female elite handball players. Fourteen Slovenian and Suisse national team players were monitored over a 7-year period by means of semi-structured interviews and official handball records. At the end of the examination period, six still-active players were interviewed again. Qualitative thematic analysis was employed to develop a contextualized understanding of participants` careers paths and life trajectories in relation to their athletic migration and dual career. In relation to the limited opportunities offered by small countries with middle-ranking national handball teams, participants highlighted that sport migration coupled with dual career opportunities represented a strategic decision for a successful career development through several key factors: (1) a clear intention towards a professional handball career; (2) the actual fulfilment of professional handball career aspirations; (3) dual career goals as part of the migration process; (4) high personal ambition and emotional connection to handball; (5) the implementation of a successful dual career path; (6) a positive migration experience; and (7) feeling supported and valued during relocation. Sport federations and elite clubs should consider the implementation of a multidimensional approach encompassing dual career paths to facilitate athletes` transnational relocation and career transitions.